Substance use profile among the first episode and clinical high-risk patients in South-West Finland - Tuunanen, Laura (My University, 2022)
The aim of this study was to evaluate prevalence of substance use among first-episode psychosis (FEP) and clinical high-risk (CHR) patients in the hospital district of Southwest Finland, compared to the general population. The sample (n = 356) included in- and outpatients from the psychiatric clinics of the City of Turku and the Hospital district of Southwest Finland. Information concerning self-reported cigarette smoking, alcohol, cannabis and other illicit drug use was collected using questionnaires. In the FEP group, current use of tobacco (OR: 9.2, 95% CI: 3.4-24.9, p < 0.001), cannabis use during lifetime (OR: 2, 95 % CI: 1.2-3.4, p = 0.013) and past 12 months (OR: 2.3, 95 % CI: 1.3-4.3, p-value = 0.007) as well as other illicit drug use during lifetime (OR: 5.1, 95 % CI: 2.6-10.2, p-value < 0.001) and past 12 months (OR: 8, 95 % CI: 3-21.7, p-value < 0.001) was found to be significantly more prevalent than among general population controls. Respectively in the CHR group, use of tobacco (OR: 3.4, 95% CI: 1.1-10.9, p = 0.036) and other illicit drugs both during lifetime (OR: 4, 95 % CI: 1.8-9, p-value = 0.001) and past 12 months (OR: 4.8, 95 % CI: 1.5-15.2, p-value = 0.008) was more common compared to the general population. Risk-level alcohol use wasn’t more prevalent among either patient group. Our study shows that especially cigarette smoking and illicit drug use was more common among both the first-episode psychosis and clinical high-risk patients compared to the general population controls.
Keywords: first-episode psychosis, clinical high-risk for psychosis, substance use